AB182. The value of extensive transurethral resection in the diagnosis and treatment of non-muscle invasive bladder cancer with respect to the recurrence at the first follow-up cystoscopy - Qie, Yunkai (Transl Androl Urol, 2016)
OBJECTIVE: To evaluate the value of extensive transurethral resection (TUR) in the diagnosis and treatment of non-muscle invasive bladder cancer (NMIBC) and its further impact on the recurrence rate at the first follow-up cystoscopy (RR-FFC). METHODS: A retrospective review of consecutive series of 523 patients with NMIBCs who underwent TUR from June 2009 to July 2015 at our institution. Extensive TURs were performed by taking additional tumor base and marginal specimens for 317 patients (group 1). Extensive TURs were not done in the other 206 patients (group 2). Urine cytology and follow-up cystoscopy were performed at 3-mo after the initial TUR. To observe the positive findings of additional specimens and whether the diagnosis and treatment plan changed in group 1. There was also a comparison of the RR-FFC between group1 and group 2. RESULTS: There were 51/317 (16.1%) patients whose additional specimens revealed pathological findings such as Ta, T1, and carcinoma in situ (Tis) diseases. Of these positive findings, 6/51 (11.8%) were Ta stage, 16/51 (31.4%) were T1 stage, 18/51 (35.3%) were T2 stage and 11/51 (21.5%) were Tis. Due to the positive findings, 29/317 (9.1%) patients changed the final diagnosis, and 45/317 (14.2%) adjusted their post-TUR treatment plans. The RR-FFC of group 1 and group 2 were 4.7% (14/297) and 13.1% (27/206) separately (P=0.001). CONCLUSIONS: Routine extensive TUR is helpful for pathological diagnosis and the post-TUR treatment of NMIBC. Furthermore, it can significantly reduce the RR-FFC of NMIBC, especially for patients with T1 stage or high grade disease.